Exploring openness and connectedness in English class with Microsoft Teams - Rosnani, Ismail; Zuraina, Ali; Nurul Nadia, Muhammad; Fathiah Izzati, Mohamad Fadzillah; Norsuhaily, Abu Bakar (Penerbit Universiti Malaysia Pahang Al-Sultan Abdullah, 2025)
This study aims at understanding the tertiary level students’ perspectives on the openness and connectedness developed by Siemens (2005) when they engage in online learning using Microsoft Teams (MS Teams) platform. More specifically, it attempts to gauge the asynchronous mode learning English among the students using MS Teams. Also, it identifies whether there is any difference in perceptions of openness and connectedness between male and female students. The current stud university at the East Coast of Malaysia